Rethinking sponsoring : evidencing and conceptualising sponsorship as a relational practice for women's career development : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy, School of Management, Massey University, Palmerston North, New Zealand - Rao, Vasudha (Massey University, 2019)
Sponsoring has been heralded as the means to redressing women’s underrepresentation in senior leadership positions, given that mentoring has not fixed this long standing problem. Sponsors are said to influence promotion decisions, give access to those in power, and provide other support for women’s career progression. However, despite the bold claims made for its efficacy, remarkably little is known about the experiences of those involved in sponsoring relationships, resulting in limited understanding of the sponsoring process, and its benefits, challenges and wider outcomes. This research adopted a qualitative research design with a phenomenological orientation to explore the experiences of sponsoring and provides insights into the nature of the sponsoring relationship through in-depth interviews with 16 people (15 women, 1 man) in New Zealand, from different professions, background and ethnicities and at different stages of their career. Findings reveal three key dynamics shaping the character of the sponsoring relationship. Firstly, rather than an instrumental focus on career advancement, the relationship is marked by perceptions of sponsors as benevolent and giving. Secondly, nurturing, caring and friendship are central features of the relationship, with different expectations held of male and female sponsors. Finally, sponsees’ ethnic and migrant identity also shaped their experience of sponsoring, indicating that the relationship is mediated by factors other than gender alone. These findings extend scholarly and practitioner knowledge about sponsoring and its positive influence upon women’s career advancement, with important implications for sponsorship research, policy and practice. They challenge the dominant understanding of sponsoring as an instrumental exchange and enable its re-conceptualisation as a relational practice of sponsorship that is oriented to fostering the sponsee’s development. They also indicate that sponsorship is experienced as a meaningful connection that extends beyond the workplace and offers broader benefits than presently recognised. From a policy and practice perspective, the findings indicate that attention to issues of gender and ethnic discrimination, and the obligations invoked in sponsees, arising from their perception of sponsor generosity, giving, nurturing and caring’, all warrant attention in organisations seeking to implement, encourage or support sponsorship programmes. Overall, the potential of sponsoring to support women’s advancement is both more personally meaningful and more complex than current research has identified.
Keywords: Mentoring in business; New Zealand; Women executives; Career development